Collaboration and opportunism in megaproject alliance contracts: The interplay between governance, trust and culture. Issue 4 (May 2021) - Galvin, Peter; Tywoniak, Stephane; Sutherland, Janet
Highlights: The relational norms of alliance contracts do not guarantee collaboration. Trust, culture and governance choices support collaborative behavior. Interactions between these factors and managerial choices over time limit opportunism. Abstract: Alliance contracts have been introduced in megaprojects to improve the alignment of objectives, risk and reward between client and contractor. However, the relational norms of alliances are not sufficient on their own to eliminate opportunistic behaviors. This study shows that, investing in mechanisms supportive of governance, culture, and trust provides a platform upon which firms may foster collaboration and limit self-interest oriented behavior amongst alliance partners. Our qualitative case study of a major project-based organization reveals the impact of these mechanisms, and more pointedly, how they interact and often reinforce each other. Governance, culture and trust are interlinked and complementary, and managers need to reflect holistically on their interactions in order to establish collaborative, rather than opportunistic behaviors.